The Development of Ringkel Batik Motifs In Banyuates, Sampang Regency - Herlina, Yekti; Arifin, Muhammad (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2026)
The Ringkel batik motif of Banyuates possesses distinctive characteristics in its production process. In addition to being manually drawn using a canting, it is also combined with jumputan (tie-dye) and ringkel techniques. The process involves binding sections of the fabric before dyeing, resulting in specific patterns. Furthermore, the Ringkel technique is executed through stitching (dilujur) according to particular patterns, which are then integrated with hand-drawn batik. This study aims to identify the various developments of Ringkel batik motifs in Banyuates and to examine the process of creating these motifs in Banyuates, Sampang, Madura. The findings of this research are expected to be beneficial for local government authorities in recognizing and documenting the names of the developed batik motifs, as well as for batik artisans themselves. This research employs qualitative methods, including observation, interviews, and documentation. These methods are utilized to explore and identify the range of Ringkel batik motifs that have been developed in Banyuates, Sampang, Madura. The objective of this study is to provide contributions in the form of inspiration and innovation, particularly in fostering creative and critical thinking related to the development of Ringkel batik motifs in Banyuates, Sampang, Madura. Ultimately, these efforts are expected to enhance the aesthetic appeal and economic value of Ringkel batik, making it increasingly attractive and commercially valuable.